ANALISIS KESALAHAN HASIL UAS MATEMATIKA SISWA KELAS VIII SMP N 2 GALANG - Alfini Alfini; Muh. Rizal; Muh. Hasbi; Rahma Nasir (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to Getting a description of errors and factors that cause errors in doing UAS for grade VIII students of SMPN 2 Galang, knowing the teachings of 2023-2024. This research is a descriptiveresearch with a qualitative approach. The subject of this study is to take 12 students of grade VIII SMP N 2 GALANG based on the value of UAS results under the KKM and teacher recommendations that can represent the answers of other students' mistakes. The researcher selects the subject by looking at the results of the student's final semester exam. Values that are below the MMC (minimum completeness criteria) will be analyzed for errors. The standard of KKM scores set at school is 75, so that students' UAS scores that are less than 75 are analyzed for errors. The results of this study show the types of mistakes made by grade VIII students of SMP N 2 Galang based on Newman's procedure: (1) errors in understanding. (2) errors in transforming, (3) errors in process skills, and (4) errors in writing the final answer. Factors that cause errors: (1) lack of students' understanding of the material that has been taught. (2) mastery of basic mathematical skills in the form of weak mathematical computing. (3) lack of understanding of concepts that make students easily forget the material that has been learned. (4) the learning model is not optimal, so that students still have difficulties in learning mathematics and tend to consider mathematics as a difficult and confusing subject.